Efektifitas Digital Branding, Peningkatan Engagement Dan Promosi Terhadap Penjualan Produk UKM Melalui Media Sosial: Eksistensi UKM Kelurahan Batu Aji - David Humala Sitorus; Arsyad Sumantika (LPPM Universitas Putera Batam, 2023)
Business ideas are affected not only by markets, companies and competitors, but also by changes. Everyone, even large companies, must recognise this. To maintain the